THE PHYSICAL CONDITION OF THE HANDBALL ATHLETE IN GARUT - Hidayat, Hidayat; Fitri, Mustika; Paramitha, Sandey Tantra (ASEAN Journal of Sport for Development and Peace, 2023)
This study aimed to determine the physical condition of Provincial Sports Week athletes in the men's handball sport in Garut Regency. This research is a descriptive study with a sample of 14 male handball athletes. The components of physical condition measured in this study were aerobic endurance, arm muscle strength, speed, leg muscle explosive power, and agility. The instrument in this study used the Indonesian Physical Fitness Test (Agung Nugroho, FIK UNY Standardization of the Physical Condition Status of Athletes in the KONI Special Region of Yogyakarta). The results showed that the condition of the men's handball sports athletes in Garut Regency showed an average result of 81% in the good category. By doing this test, we can get some benefits for their bodies.